Critical thinking in information literacy pedagogical strategies: New dynamics for higher education throughout librarians’ vision - Sanches, Tatiana (2022)
This work explores the articulation of Information Literacy and CriticalThinking, throughout a preliminary study on the pedagogical strategies usedby academic librarians in lecturing information literacy courses. A theoreticalreflection is presented about students’ skills in Information Literacy, enhancedby Critical Thinking, to acquire the ability to move autonomously in printedand digital information environments, based on their reflective thinking, totransform information into new knowledge. The study aims to compareinformation literacy pedagogical practices in different subject areas. As such,psychology, education, and health sciences were the ecosystems in which thestrategies were explored and applied to analyze common approaches, andultimately detect and share good practices for pedagogical improvements. Thepresent work results from a qualitative study, based on the interviewsregarding the vision of three academic librarians, framed by seven majorparameters: metacognition, reflection, analysis, evaluation, inference, anduse, as well as dispositions, applied to information management. The objectivewas to evaluate what kind of strategies were adopted by each librarian and ifthe pedagogical practices are effective in fulfilling the learning objectives.Overall, all three librarians agreed that libraries have an important role inpromoting critical thinking in higher education students. (12) (PDF) Critical Thinking in Information Literacy Pedagogical Strategies: new dynamics for Higher Education throughout librarians’ vision. Available from: https://www.researchgate.net/publication/361286257_Critical_Thinking_in_Information_Literacy_Pedagogical_Strategies_new_dynamics_for_Higher_Education_throughout_librarians'_vision [accessed Sep 27 2022].